Heavy Metal Poisoning and Its Impacts on the Conservation of Amazonian Parrots: An Interdisciplinary Review - Marina Sette Camara Benarrós; Ketelen Ayumi Corrêa Sakata; Brenda Juliane Silva dos Santos; Felipe Masiero Salvarani (Biology, 2025)
Amazonian parrots (Psittacidae) are essential to ecosystem balance. Already vulnerable to habitat fragmentation and weak environmental regulations, they are now increasingly threatened by heavy metal contamination. This review synthesizes evidence on the sources, transgenerational bioaccumulation, and physiological impacts of metals such as mercury (Hg), lead (Pb), cadmium (Cd), zinc (Zn), and arsenic (As) in these birds. Anthropogenic activities, including illegal gold mining, agricultural intensification, and urban expansion, release metals that biomagnify along food webs. Parrots, as long-lived, high-trophic consumers, accumulate metals in vital tissues, leading to severe neurotoxic effects, immunosuppression, reproductive failure, and reduced survival. Furthermore, maternal transfer of contaminants to eggs exacerbates genetic erosion and threatens population viability. While biomonitoring tools and habitat restoration have been proposed, current strategies are insufficient against the synergistic pressures of pollution and climate change. Addressing heavy metal exposure is critical to conserving Amazonian biodiversity and safe-guarding ecosystem services. Future efforts should prioritize multidisciplinary predictive models, bioremediation actions, and the strengthening of international environmental governance to ensure the survival of these sentinel species.